Factors Influencing Critical Care Nurses’ Mental Workload: A Scoping Review - Farida Farida; Bagoes Widjanarko; Luky Dwiantoro (Indonesian Journal of Global Health Research, 2025)
The mental workload of critical care nurses significantly impacts their well-being, job satisfaction, and overall performance, ultimately affecting the quality of care in critical care environments. This study aimed to identify and categorize the factors influencing mental workload among critical care nurses through a scoping review guided by Arksey and O'Malley’s framework. A comprehensive literature search across five databases (PubMed, ScienceDirect, EBSCOhost - CINAHL Complete, Medline, and Scopus) resulted in the inclusion of 8 relevant studies, which examined the psychosocial, organizational, and environmental factors contributing to critical care nurses' mental workload. The findings revealed that mental workload is influenced by a range of factors, including nurse-to-patient ratios, patient complexity, demographic characteristics (such as age and experience), and psychosocial stressors such as job dissatisfaction, lack of organizational support, and high emotional demands. Additionally, higher patient loads, long shifts, and inadequate support systems were identified as key contributors to mental strain, leading to increased fatigue, burnout, and reduced job satisfaction. The study emphasized the critical role of organizational support, motivation, and leadership in mitigating mental workload. Interventions aimed at improving staffing, work conditions, and leadership quality, alongside the reduction of excessive patient loads, are essential for enhancing nurse resilience, reducing burnout, and ultimately improving patient care outcomes in critical care settings.